2019
DOI: 10.1155/2019/7817809
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Robust Blind Watermarking Scheme Improved by Entropy‐Based SVM and Optimized Quantum Genetic Algorithm

Abstract: With the intensive study of machine learning in digital watermarking, its ability to balance the robustness and transparency of watermarking technology has attracted researchers’ attention. Therefore, quantum genetic algorithm, which serves as an intelligent optimized scheme combined with biological genetic mechanism and quantum computing, is widely used in various fields. In this study, an adaptive robust blind watermarking algorithm by means of optimized quantum genetics (OQGA) and entropy classification-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Earlier digital watermarking technologies [1,2] focused on grayscale images, and watermarks were embedded in spatial or frequency domains. With the development of artificial intelligence and the special demand for host images, adaptive watermarking [3,4], reversible watermarking [5], and deep learning watermarking [6] have received attention. In recent years, watermarking has been required to achieve higher robustness, and researchers expect more purposes are packed in a watermarking scheme; thus, it promotes the development of multipurpose watermarking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier digital watermarking technologies [1,2] focused on grayscale images, and watermarks were embedded in spatial or frequency domains. With the development of artificial intelligence and the special demand for host images, adaptive watermarking [3,4], reversible watermarking [5], and deep learning watermarking [6] have received attention. In recent years, watermarking has been required to achieve higher robustness, and researchers expect more purposes are packed in a watermarking scheme; thus, it promotes the development of multipurpose watermarking.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Step 2: use the layer R and the layer G to generate hash sequence. (3) Step 3: embed the watermark sequence in the layer B using the LSB embedding method[20] (4). Step 4: repeat steps 2-3 until all the blocks are processed.ALGORITHM 3: Embedding fragile watermark.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [36] and Zhang et al [37] apply ergodic matrix in the image encryption scheme and obtain a good result. It is demonstrated that an ergodic matrix with proper parameters [36,37] can be employed to completely shuffle the original image and has an immense key space of at least3.08×10 5898 . Therefore, the same method is used in watermark preprocessing in our research.…”
mentioning
confidence: 99%
“…Therefore, the same method is used in watermark preprocessing in our research. For preprocessing is not our main concern, interested readers can refer to [36,37] .…”
mentioning
confidence: 99%